The human side of project leadership - Amason, Allen C.; Reilly, Richard R. (Project Management Institute, 2007)
Good leadership skills enable a project manager to harness the energy and capabilities of a project team in such a way that the performance of the team is greater than the sum of its parts. Often referred to as the "human side" of project management or "people skills," leadership is widely accepted as the critical factor in determining the ultimate success or failure of a project. The Human Side of Project Leadership is a collection of academic studies related to the human side of project management. Taken as a group, these three studies illuminate the ways in which leadership, project spirit and conflict management skills impact project success.
Keywords: Project management.; Leadership.; Conflict management.; elektronické knihy; electronic books